A molecular basis for spine color morphs in the sea urchin Lytechinus variegatus - Maria Wise; Madison Silvia; Gerardo Reyes; Rushane Dunn; Thomas M. Onorato; Cosmo Pieplow; Aidan Furze; El Hebert; Nathalie Oulhen; Dan Ritschoff; David R. McClay; Gary Wessel (Scientific Reports)
Abstract Animals of the phylum Echinodermata are characterized by a pentaradially symmetric endoskeleton in adults. Echinoids also have endoskeletal spines ranging in length from several millimeters (sand dollars e.g. Mellita quinquiesperforata of the order Clypeasteroida) to 30 cm (the black sea urchin, Diadema antillarum of the order Euechinoidea). Here we integrate an analysis of genetic, structural and molecular properties of spines from the variegated sea urchin, Lytechinus variegatus. Through genetic crosses we learned that white is dominant over red and green colors, and that pigmentation follows classic Mendelian genetics. The abundance of mRNAs encoding flavin mono-oxygenase variancts and polyketide synthase was predictive of the color of the adult and antibodies identified their histological location in the spine cells. By RNA in situ hybridization, candidate genes important for spine biomineralization and pigmentation were mapped onto the spine epithelia, and MicroCT scans of spines from different color morphs concluded that color morphs are entirely due to pigmentation and not to structural variations of the endoskeleton. By confocal microscopy we localized gene expression along and within the spines and learned that genes involved in pigment biosynthesis showed selective distribution along the spine. Spine epidermis is mitotically active and red spherule immunocytes are highly migratory within the spine. Overall the results provide a key foundation for examining the mechanisms of molecular diversity and patterning in the name sake of the phylum Echinodermata.